Influence of post-cure treatments on hardness and marginal adaptation of composite resin inlay restorations: an in vitro study - Laiza Tatiana Poskus; Antonio Marcelo Accetta Latempa; Maurício Alves Chagas; Eduardo Moreira da Silva; Mariana Pareira da Silva Leal; José Guilherme Antunes Guimarães (University of São Paulo, 2009)
OBJECTIVES: The purpose of this study was to evaluate the Vickers hardness number (VHN) and the in vitro marginal adaptation of inlay restorations of three hybrid composite resins (Filtek Z250, Opallis and Esthet-X) subjected to two post-cure treatments. MATERIAL AND METHODS: For the microhardness test, three different groups were prepared in accordance with the post-cure treatments: control group (only light cure for 40 s), autoclave group (light cure for 40 s + autoclave for 15 min at 130ºC); and microwave group (light cure for 40 s + microwave for 3 min at 450 W). To assess the marginal adaptation, the composite resin was inserted incrementally into a mesial-occlusal-distal cavity brass mold and each increment light-cured for 40 s. A previous reading in micrometers was taken at the cervical wall, using a stereomicroscope magnifying glass equipped with a digital video camera and image-analysis software. Subsequently, the specimens were subjected to the post-cure treatments (autoclave and microwave) and a reading was taken again at the cervical wall. Data were compared using ANOVA for the hardness test, split-plot ANOVA for the adaptation assessment and Tukey's test for multiple comparisons. A significance level of 5% was adopted for all analyses. RESULTS: The post-cure treatments increased the hardness of conventional composites (p<0.001) and the gap values of inlay restorations (p<0.01). Filtek Z250 showed higher hardness (p<0.001) and lower gap values than Opallis and Esthet-X (p<0.05). Gap values did not exceed 90 µm for any of the experimental conditions. CONCLUSION: The post-cure treatments increased the VHN and the gap values on the cervical floor of composite resin inlays. Moreover, Filtek Z250 showed the best results, with higher hardness and lower gap values.